Nutrient accumulation at the initial growth of pitaya plants according to phosphorus fertilization - Rodrigo Amato Moreira; Maria do Céu Monteiro da Cruz; Denison Ramalho Fernandes; Enilson de Barros e Silva; Jéssica de Oliveira (Pesquisa Agropecuária Tropical, 2016)
The knowledge about the amount of nutrient uptake in pitaya plants helps the balanced fertilizer recommendation for the crop, providing adequate nutrition and contributing to the maximum expression of this species potential. This research was carried out in order to evaluate the growth, nutrient accumulation and efficiency of absorption, transportation and use of P by pitaya according to phosphorus fertilization. A randomized blocks design was used, with five doses of P (0 mg dm-3, 20 mg dm-3, 40 mg dm-3, 80 mg dm-3 and 160 mg dm-3) incorporated into the soil, with four replications, three pots per plot and one cutting per pot. Differences in the nutrient accumulation of all doses were evident in the pitaya shoots and roots, as well as in the efficiency of absorption, transport and use of P, according to phosphorus fertilization. The nutrient accumulation in the pitaya roots was ranked in the following order: N > K > Ca > S > P > Mg > Fe > Mn > Zn > B ≥ Cu. For the shoots, the order was: K > N > Ca > S > Mg > P > Mn > Fe > Zn > B ≥ Cu. The initial growth of pitaya plants was maximum with 81 mg dm-3 of P, in a Red-Yellow Dystrophic Latosol. The application of 44-67 mg dm3 of P to the soil promoted the highest accumulation of macro and micronutrients in the pitaya.